Digital Transformation and Managerial Accounting in Improving the Accountability of Public Organizations - Dahnil Anzar Simanjuntak; Fajar Rezeki Ananda Lubis (Jurnal Ilmiah Akuntansi Kesatuan, 2026)
Increasing demands for transparency and responsible financial management in public organizations have highlighted the need for both technological and managerial improvements. This study aims to examine the influence of digital transformation and managerial accounting on the accountability of public organizations. A causal explanatory quantitative approach was employed, with primary data collected from 100 respondents across regional apparatus organizations and analyzed using multiple linear regression. The results indicate that both digital transformation and managerial accounting have positive and significant effects on public organization accountability, both partially and simultaneously. Managerial accounting is the more dominant factor, suggesting that effective use of cost information for planning, control, and performance evaluation is crucial alongside technological advancement. The model explains 68.5% of the variation in accountability. This study contributes by integrating digital transformation and managerial accounting in a single framework and providing empirical evidence from a local government context. The findings imply that aligning digital infrastructure with strong managerial accounting practices is essential for achieving sustainable and comprehensive accountability in public sector governance.